Gut microbiota and its importance in the development of obesity and insulin resistance - Barton, Karolina (2021)
Obesity and insulin resistance are significant predisposing causes of co-existing diseases such as type 2 diabetes, non-alcoholic fatty liver disease, cardiovascular and neurodegenerative disorders, and several types of cancer. Global obesity prevalence continues to accelerate and now affects a high number of people. Research has reported that lean and obese rodents and humans may exhibit variations in gut flora composition. Evidence from diverse sources indicates a significant association between gut microbiota and obesity/insulin resistance during the last years. Diet-related obesity promotes insulin resistance through mechanisms independent and dependent on the gut microbiota. Polyphenols, ketones, short-chain fatty acids and fibres can act on the gut microbiota, promoting beneficial bacteria and inhibiting the growth of pathogenic bacteria. However, some elements promote the development of undesirable bacteria in the gut, such as highly processed foods with extended shelf-life ingredients, excessive fructose consumption, and processed trans fatty acids. The gut microbiota is an important target for treating and preventing inflammation and metabolic disorders in human. This literature review examines several factors explaining the relationship between gut flora, and metabolic disorders such as insulin resistance and obesity. The influence of food on the modulation of bacterial composition in the gut and its consequences in the context of chronic diseases are also described.